POSITION OF LAMURU CORN SEED FARMING IN TARUS FOOD CROP SEED CENTER, KUPANG DISTRICT - Lambertus Nesi Bria; Umbu Joka (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
Lamuru corn is one of the certified superior seeds cultivated by the Tarus Food Crops Center (BBI) of Kupang Regency. Apart from producing Lamuru corn seeds, BBI has also carried out marketing activities since its establishment in the 1990s until now. This study aims to determine the position of Lamuru corn seed farming through the Boston Consulting Group matrix approach. Data collection techniques used the Focus Group Discussion method. The types of data in this study are primary and secondary data. The research population was all farmers who worked at the Tarus Food Crops Main Seed Center, consisting of 14 farmers. Sampling uses a census or saturated sample method in which the entire population is used as a sample. The results showed that Lamuru corn seed farming at the Tarus Food Crops Main Seed Center was in a star position. This position indicates that lamuru corn seed farming has a high market growth rate of 94.77% and a market share of 0.8 times. The policy implies empowering farmers/breeders/KSO (Operational Cooperation) by increasing the area of ​​land that is the responsibility of BBI Tarus of 7 Hectares.